Governança presidencial, políticas públicas e desenvolvimento - Antônio Lassance (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This Discussion Paper presents an introductory approach to presidential governance in Brazil. The historical institutionalism framework, the comparative historical method, and the policy-focused political analysis are used in this approach which consists in highlighting the critical component of presidential governance to public policy and development. The research is specifically designed to the study of unilateral action, more precisely, the presidential decrees. The result is the finding of eight presidential governance patterns, extracted from the combination of presidential decisions on the field of public administration or economic and social regulation, and also analyzing the mechanisms of incentive and restriction (or punishment) used by presidents when in government.
Keywords: P11; 330; state; development; government; governance; public policy; democracy; presidential studies; presidentialism